2014
DOI: 10.1371/journal.pone.0091006
|View full text |Cite
|
Sign up to set email alerts
|

PGC-1α-Mediated Branched-Chain Amino Acid Metabolism in the Skeletal Muscle

Abstract: Peroxisome proliferator-activated receptor (PPAR) γ coactivator 1α (PGC-1α) is a coactivator of various nuclear receptors and other transcription factors, which is involved in the regulation of energy metabolism, thermogenesis, and other biological processes that control phenotypic characteristics of various organ systems including skeletal muscle. PGC-1α in skeletal muscle is considered to be involved in contractile protein function, mitochondrial function, metabolic regulation, intracellular signaling, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 87 publications
(104 citation statements)
references
References 32 publications
6
95
0
Order By: Relevance
“…This cohort comprises genes involved in mitochondrial trafficking (Rab26, Ostm1, and Pon3) and those involved in amino acid metabolism (Aass, Bckdk, Gcdh, Qtrt1, and Wdyhv1) (Hutson 2006;Cleveland et al 2008;Wang et al 2009;Biela et al 2013;Seminotti et al 2013;Hatazawa et al 2014). The three trafficking genes seem to be involved in interactions between mitochondria and lysosomes as mentioned (Rab26 and Ostm1) and between mitochondria and the ER (Pon3).…”
Section: Discussionmentioning
confidence: 99%
“…This cohort comprises genes involved in mitochondrial trafficking (Rab26, Ostm1, and Pon3) and those involved in amino acid metabolism (Aass, Bckdk, Gcdh, Qtrt1, and Wdyhv1) (Hutson 2006;Cleveland et al 2008;Wang et al 2009;Biela et al 2013;Seminotti et al 2013;Hatazawa et al 2014). The three trafficking genes seem to be involved in interactions between mitochondria and lysosomes as mentioned (Rab26 and Ostm1) and between mitochondria and the ER (Pon3).…”
Section: Discussionmentioning
confidence: 99%
“…Western blot analysis. Western blot analysis was performed as described previously (13). Densitometric analysis was done using ImageJ software (http://rsb.info.nih.gov/ij/index.html).…”
Section: Methodsmentioning
confidence: 99%
“…Leucine stimulates skeletal muscle PPARβ/δ 11 reduced cellular ATP content), however leucine appears to also function through additional mechanisms (such as heightened expression of leucine degradation enzymes [31,32] and/or through the activation of the eNOS/NO/cGMP/SIRT pathway leading to increased mitochondrial content) [31]. The expression of leucine degradation enzymes are regulated by PPARα and PGC-1α, and it has been suggested that increased mitochondrial content/enzyme content is necessary to support BCAA clearance [31,32].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%